2018
DOI: 10.3389/fmicb.2018.00213
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Sex Affect Diverse Microbial Niches within the Gut

Abstract: Gut microbiota is considered a separate organ with endocrine capabilities, actively contributing to tissue homeostasis. It consists of at least two separate microbial populations, the lumen-associated (LAM) and the mucosa-associated microbiota (MAM). In the present study, we compared LAM and MAM, by collecting stools and sigmoid brush samples of forty adults without large-bowel symptoms, and through a 16S rRNA gene next-generation sequencing (NGS) approach. MAM sample analysis revealed enrichment in aerotolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
83
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 63 publications
12
83
1
Order By: Relevance
“…In human studies, higher abundances of Ruminococcus species (such as Ruminococcus bromii and Ruminococcus obeum ) were also observed in obese subjects (Kasai et al 2015), however, some Ruminococcaceae bacteria such as Dialister, Methanobrevibacter , and Oscillospira have also been associated with lower BMI (Jumpertz et al 2011; Goodrich et al 2014). From our data, we identified 17 OTUs assigned to Ruminococcaceae were significantly correlated with BMI, and many of which were inversely correlated with BMI including the well-studied butyrate producer Faecalibacterium prausnitzii , which is consistent with several studies (Borgo et al 2018; Tilg and Moschen. 2014).…”
Section: Discussionsupporting
confidence: 88%
“…In human studies, higher abundances of Ruminococcus species (such as Ruminococcus bromii and Ruminococcus obeum ) were also observed in obese subjects (Kasai et al 2015), however, some Ruminococcaceae bacteria such as Dialister, Methanobrevibacter , and Oscillospira have also been associated with lower BMI (Jumpertz et al 2011; Goodrich et al 2014). From our data, we identified 17 OTUs assigned to Ruminococcaceae were significantly correlated with BMI, and many of which were inversely correlated with BMI including the well-studied butyrate producer Faecalibacterium prausnitzii , which is consistent with several studies (Borgo et al 2018; Tilg and Moschen. 2014).…”
Section: Discussionsupporting
confidence: 88%
“…For example, when the sheep were subjected to cold treatment, the abundance ofLachnospiraceae_XPB1014, which is highly enriched in the gut of nonalcoholic fatty liver patients [24], increased, and the abundance of Prevotellaceae_UCG003 decreased. These two bacterial taxa represent more than 1% of the bacterial community in the rumen anduse dietarysoluble ber as substrate to produce short chain fatty acids [25].Furthermore, several nitrogen-xing microbial groups, such asDevosia and Rhizobium [26], were enriched in the wind-exposed sheep, which might increase the amount of ammonia and urea produced via the rumen nitrogen cycle. As a result, the abundance of Brachybacterium increased, which uses urea to breed and degrade harmful substancessuch asphenol [27].…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is our adjustment for age, sex, and BMI. Several studies have suggested that the composition of the human gut microbiota changes with age and is associated with obesity and gender [26][27][28][29][30][31]. We excluded the influence of these factors by using the propensity score matching, which might have caused the differences compared to the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%